The Factor Affecting Medication Adherence in Tuberculosis Patients: A Literature Review - Daimah Wirdatus Sanaun Harahap; Retnosari Andrajati; Santi Purna Sari; Diah Handayani (Eduvest - Journal of Universal Studies, 2025)
Medication adherence is crucial for the successful treatment of tuberculosis (TB), a persistent global health issue that demands prolonged and rigorous therapy to achieve cure, prevent drug resistance, and reduce transmission rates within communities. Recent studies highlight predictors of effective treatment outcomes such as being a new TB case and being HIV-negative. There is a significant relationship between various psychosocial factors that influence treatment adherence, particularly among elderly TB patients, where adherence is characterized by complexity and multidimensionality. Factors like depression, anxiety, income levels, social support, patient status, and TB classification play critical roles in adherence. Understanding these factors is essential for optimizing treatment strategies and improving outcomes in TB management.